Annual fire resilience of ground‐dwelling ant communities in Hiraodai Karst Plateau grassland in Japan. Issue 2 (4th November 2014) - Hosoishi, Shingo; Tasen, Wattanachai; Park, Sang‐Hyun; Le Ngoc, Anh; Kuboki, Yuzuru; Ogata, Kazuo
Abstract The fire resilience of ground‐dwelling ant assemblages in grassland subjected to annual fire management was investigated. Study sites consisted of three burnt sites and three unburnt sites in grasslands on the Hiraodai Karst Plateau in Fukuoka Prefecture, Japan. Ground‐dwelling ants were sampled by Winkler extraction and collected at 10 days and 1, 2, 3 and 6 months post‐fire. In total 33 ant species belonging to 25 genera in six subfamilies were collected from the burnt and unburnt sites. Eight of the 29 ant species collected at burnt sites were restricted to burnt sites, while four of the 25 ant species collected at unburnt sites were restricted to unburnt sites. Non‐metric multidimensional scaling and analysis of similarities revealed that the ant assemblages in the burnt sites at 10 days and 1 month post‐fire were clearly separated from the assemblages observed at 2, 3 and 6 months post‐fire. The results suggested that the ground‐dwelling ant fauna in the study area were highly resilient to fire at 2 months post‐fire and that the annual fire regime did not have a marked effect on species richness.